Safety and outcomes of routine endovascular thrombectomy in large artery occlusion recorded in the SITS Register: An observational study - Ahmed, N; Mazya, M; Nunes, A P; Moreira, T; Ollikainen, J P; Escudero-Martinez, I; Bigliardi, G; Dorado, L; Dávalos, A; Egido, J A; Tassi, R; Strbian, D; et al. (Journal of internal medicine, 2021)
BACKGROUND AND OBJECTIVE: We aimed to evaluate the safety and outcomes of thrombectomy in anterior circulation acute ischaemic stroke recorded in the SITS-International Stroke Thrombectomy Register (SITS-ISTR) and compare them with pooled randomized controlled trials (RCTs) and two national registry studies. METHODS: We identified centres recording ≥10 consecutive patients in the SITS-ISTR with at least 70% of available modified Rankin Scale (mRS) at 3 months during 2014-2019. We defined large artery occlusion as intracranial internal carotid artery, first and second segment of middle cerebral artery and first segment of anterior cerebral artery. Outcome measures were functional independence (mRS score 0-2) and death at 3 months and symptomatic intracranial haemorrhage (SICH) per modified SITS-MOST. RESULTS: Results are presented in the following order: SITS-ISTR, RCTs, MR CLEAN Registry and German Stroke Registry (GSR). Median age was 73, 68, 71 and 75 years; baseline NIHSS score was 16, 17, 16 and 15; prior intravenous thrombolysis was 62%, 83%, 78% and 56%; onset to reperfusion time was 289, 285, 267 and 249 min; successful recanalization (mTICI score 2b or 3) was 86%, 71%, 59% and 83%; functional independence at 3 months was 45.5% (95% CI: 44-47), 46.0% (42-50), 38% (35-41) and 37% (35-41), respectively; death was 19.2% (19-21), 15.3% (12.7-18.4), 29.2% (27-32) and 28.6% (27-31); and SICH was 3.6% (3-4), 4.4% (3.0-6.4), 5.8% (4.7-7.1) and not available. CONCLUSION: Thrombectomy in routine clinical use registered in the SITS-ISTR showed safety and outcomes comparable to RCTs, and better functional outcomes and lower mortality than previous national registry studies.
Keywords: Thrombectomy; Stroke; Retrospective Studies; Brain Ischemia; výsledek terapie; arterie; cévní mozková příhoda; trombektomie; Intracranial Hemorrhages; Randomized Controlled Trials as Topic; retrospektivní studie; Humans; intrakraniální krvácení; endovaskulární výkony; Endovascular Procedures; randomizované kontrolované studie jako téma; ischemie mozku; Treatment Outcome; Arteries; lidé